THE PRIMACY OF SOCIAL NETWORKS IN ENTREPRENEURSHIP: A STUDY OF NETWORKING ABILITY AND INNOVATIVENESS AMONG UNIVERSITY STUDENTS IN NORTH CENTRAL NIGERIA
The study; The Primacy of Social Networks in Entrepreneurship: A Study of Social Networking Ability and Innovativeness among University Students in North Central Nigeria, ascertained the relationship between networking ability and innovativeness. To achieve this, a correlational survey of 402 respondents being the students of the five selected universities was conducted. The study used primary data that were generated using structured questionnaires that were administered on the selected respondents. Descriptive statistics, correlation and other diagnostics were used to analyse the data and to test the hypothesis. The study found a strong correlation between networking ability and innovativeness (r=0.336, p0.05